OS DESAFIOS E OS ESFORÇOS DA CADEIA PRODUTIVA DA CONSTRUÇÃO CIVIL PARA A ADOÇÃO DO BIM - Freitas, Raissa Caroline Faria; Melhado, Silvio; Cardoso, Francisco Ferreira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
It is widely known that the Construction Sector production chain is fragmented and, consequently, has an increasingly need to enhance competitiveness through technological advancements. This is even more important in Brazil, since this production chain`s productivity is inferior when compared to others from the same country and also inferior when compared to the same production chain from other countries. BIM methodology is acknowledged by several authors as the key to achieve a better product, since it can bring many benefits for all the agents in this production chain. Moreover, there are also numerous barriers encountered during BIM adoption and usage, many of them are covered in this article. This paper also analyses the efforts for BIM diffusion throughout the country in sectorial and governmental levels.